La pensée de la race en Italie Du romantisme au fascisme - Aramini, Aurélien; Bovo, Elena (Les Cahiers de la MSHE Ledoux, 2018)
The importance of the italian idea of race has been underestimated for a long time. Therefore, in Italy as well as in France or in Germany, a certain number of literary works or scientific discourses mobilise the concept of race in a theoretical and political perspective. From the first decades of the 19th century to the fascist period, three points - romantic philology, positivist anthropology and fascist ideology - prepare the ground of the Italian idea of race. The study of these points reveal a specific use engaging not only the relation the Peninsula maintains with the other but also the relation it maintains with itself.